Leveraging Every Door Direct Mail for remote recruitment of a rural Appalachian study Sample: Response rate and representativeness - Khawlah S. Al-Muhanna; Katharine Garrity; Zoë T. Plakias; Andrew Hanks; Kathleen Krzyzanowski Guerra; Jennifer A. Garner (Preventive Medicine Reports, 2023)
Every Door Direct Mail (EDDM) is a service of the United States Postal Service (USPS) that delivers non-addressed mail to all postal customers on designated mailing routes. Primarily used for marketing, we describe EDDM’s efficacy as a research tool for remotely recruiting a representative convenience sample of rural Appalachian households for a longitudinal survey-based health study. In June 2020, recruitment postcards were sent via EDDM to all residential addresses (n = 31,201) within an 18 ZIP code region of Southeastern Ohio. Adults were invited to complete a survey online via QR code or to call for a mailed survey. Respondent demographic characteristics were generated using SPSS and compared with the region’s 2019 U.S. Census Bureau statistics. A total of 841 households responded to the invitation, reflecting a response rate higher than marketing estimates (2.7 % vs 2 %). Compared to Census data, a greater proportion of respondents were female (74 % vs 51 %), and highly educated (64 % vs 36 % college graduates); a comparable proportion were non-Hispanic (99 % vs 98 %), white (90 % vs 91 %), and had ≥ 1 adult in the household (1.7 ± 0.9); and a lower proportion had a household income < $50 k (47 % vs 54 %). The median age was higher (56 vs 30 years), and 29 % were retirees. EDDM was a viable method for remote recruitment of a rural geographically-based sample. Further work is needed to explore its efficacy in recruiting representative samples in other contexts and to inform best practices for its use.